The recent development of topical nanoparticles for annihilating skin cancer - Dnyanesh Saindane; Sankha Bhattacharya; Rahul Shah; Bhupendra G. Prajapati (All Life, 2022)
Nanoparticles open up new possibilities for treating skin problems. For the treatment of numerous skin problems, the topical route of administration has many advantages. This method avoids the hepatic first-pass impact, and many medications’ systemic availability is limited to skin cells like hair follicles, reducing undesired side effects and increasing localised therapeutic benefit. The skin's barrier function makes it difficult for nanoparticles to penetrate the tissue, even if the barrier is partially impaired in cases of damage or inflammation, such as in skin cancer. This could make nanoparticle penetration easier. Although a lot of work has gone into producing nanoparticles for topical distribution, there has been very little success in getting them to the clinic to treat skin malignancies. We review the various forms of skin malignancies and current clinical care strategies. Clinical therapy and management are also illustrated, explaining various skin cancer treatment options. In a brief manner, this study also emphasises the various nanoformulations that are being explored and reported, as well as the various types of nanoparticle systems. Hghlights Skin cancer is one of the widely occurring disease worldwide with varying mortality rates. Clinical supervision of skin cancer is crucial as it may lead to some serious consequences. Nanoparticle/nanovesicle systems would aid in better treatment and reduced adverse effects. Different nano systems are currently under development for the topical treatment of skin cancer. Penetration analysis of NPs is also important to develop a topical novel nanoformulation. Abbreviations: NMSC, non-melanoma skin cancer; MSC, melanoma skin cancer; BCC, basal cell carcinoma; cSCC, cutaneous squamous cell carcinoma; SC, stratum corneum; BCS, biopharmaceutics classification system; UV, ultraviolet; WHO, World Health Organization; AK, actnic keratosis; PDT, photo dynamic therapy; 5-FU, 5-fluorouracil; nm, nanometre; mV, millivolts; FDA, Food and drug administration; API, active pharmaceutical ingredient; NPs, nanoparticles; SLNs, solid-lipid nanoaparticles; NLCs, nanostructured lipid carriers; AuNPs, gold nanoparticles; QDs, quantumn dots; CNTs, carbon nanotubes